2016
DOI: 10.1007/s11948-016-9818-6
|View full text |Cite
|
Sign up to set email alerts
|

Science Outside the Lab: Helping Graduate Students in Science and Engineering Understand the Complexities of Science Policy

Abstract: Helping scientists and engineers challenge received assumptions about how science, engineering, and society relate is a critical cornerstone for macroethics education. Scientific and engineering research are frequently framed as first steps of a value-free linear model that inexorably leads to societal benefit. Social studies of science and assessments of scientific and engineering research speak to the need for a more critical approach to the noble intentions underlying these assumptions. "Science Outside the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
10
0
2
Order By: Relevance
“…The sense of job satisfaction reported by participants arose from the learning opportunities associated with working in a diverse team, as well as a sense of personal achievement from observing tangible impacts of science on policy and practice. Indeed, previous studies have shown that while many environmental scientists, particularly early career scientists, are driven by a personal goal of achieving impacts on policy and practice, they are not skilled or trained in how engage with decision-makers, nor understand the complexities of policy processes [ 8 , 55 ]. This can lead to reduced career satisfaction among early-career scientists, making them less likely to pursue a long-term career in science [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sense of job satisfaction reported by participants arose from the learning opportunities associated with working in a diverse team, as well as a sense of personal achievement from observing tangible impacts of science on policy and practice. Indeed, previous studies have shown that while many environmental scientists, particularly early career scientists, are driven by a personal goal of achieving impacts on policy and practice, they are not skilled or trained in how engage with decision-makers, nor understand the complexities of policy processes [ 8 , 55 ]. This can lead to reduced career satisfaction among early-career scientists, making them less likely to pursue a long-term career in science [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the pursuit of developing scientists who understand and can effectively engage with policy processes (Tyler, 2017), many organisations now offer formal opportunities for scientists to learn about and experience policymaking in practice (AAAS, 2017;Bernstein et al, 2017;Kuehne et al, 2014;Petes and Meyer, 2018). These provide important avenues for ECRs to gain firsthand experience of operating at the interface of science and policy.…”
Section: Institutionsmentioning
confidence: 99%
“…Despite this academic progress, however, the practicalities of how to successfully influence policy processes that are laden with diverse ideas, values and norms can remain elusive to many scientists. This is particularly pertinent among early career researchers (ECRs), with evidence showing that while achieving policy impact is an important personal goal for many ECRs (including postgraduate students), they are not always skilled or trained in how to engage with decision-makers, nor understand the complexities of policy processes (e.g., Bernstein et al, 2017;Cvitanovic, Hobday, van Kerkhoff and Marshall, 2015;Marcella et al, 2017). Further, ECRs must not only navigate trade-offs inherent in balancing science-policy work with their research (Sarkki et al, 2014), but to do so in a highly insecure career stage characterised by short-term contracts and extreme mobility (Kellard and Śliwa 2016;Phillips and Heywood-Roos, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…SOtL is typically held in Washington, DC and brings together approximately 14 science and engineering doctoral students. Over the course of one or two weeks, the students meet dozens of people who work at the interface of engineering, policy, and society including policymakers, regulators, funders, lobbyists, lawyers, and museum professionals (Bernstein et al 2016).…”
Section: Science Outside the Labmentioning
confidence: 99%